Bacteriophages as Biotechnological Tools - Mariana Alves Elois; Raphael da Silva; Giulia Von Tönnemann Pilati; David Rodríguez-Lázaro; Gislaine Fongaro (Viruses, 2023)
Bacteriophages are ubiquitous organisms that can be specific to one or multiple strains of hosts, in addition to being the most abundant entities on the planet. It is estimated that they exceed ten times the total number of bacteria. They are classified as temperate, which means that phages can integrate their genome into the host genome, originating a prophage that replicates with the host cell and may confer immunity against infection by the same type of phage; and lytics, those with greater biotechnological interest and are viruses that lyse the host cell at the end of its reproductive cycle. When lysogenic, they are capable of disseminating bacterial antibiotic resistance genes through horizontal gene transfer. When professionally lytic—that is, obligately lytic and not recently descended from a temperate ancestor—they become allies in bacterial control in ecological imbalance scenarios; these viruses have a biofilm-reducing capacity. Phage therapy has also been advocated by the scientific community, given the uniqueness of issues related to the control of microorganisms and biofilm production when compared to other commonly used techniques. The advantages of using bacteriophages appear as a viable and promising alternative. This review will provide updates on the landscape of phage applications for the biocontrol of pathogens in industrial settings and healthcare.